INDOGLISH USED BY MOBILE LEGENDS PLAYERS ON INSTAGRAM - Dina Fitri, Dwi; Tahrun; Ana Theriana (Universitas PGRI Palembang, 2024)
This study investigates the use of Indoglish a mix of Indonesian and English as a sociolinguistic phenomenon among Mobile Legends players on a social media with around 56% Indonesian population are using named Instagram. Involves the integration of Indonesian linguistic elements with English vocabulary through qualitative methods: observations, interviews and documentation. The formation likely English nouns and adjectives with Indonesian prefixes (di-, nge-, se-) and suffixes (-nya, -an). Prominent Indoglish phrases like